An Experimental Investigation to Evaluate Gas Flow Characteristics of Coal - McPherson M. J (The Australasian Institute of Mining and Metallurgy, 1988)
An experimental investigation was carried out to determine the various gas flow characteristics of bituminous coal samples. Adsorption and desorption tests were first conducted to estimate the quantity of methane that is retained by coal, and the rate at which it is released. Experiments were then carried out to study the variation in coal permeability with changes in applied stress and gas pressure - factors that change continuously with time. To further understand the phenomena involved in retention, release, and flow of gas, electron microscopy was used to study the microstructure of coal and how it affects these characteristics of coal.